2017
DOI: 10.1590/s0100-204x2017000800012
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic diversity in buffalo cows of the Jafarabadi, Murrah, and Mediterranean breeds

Abstract: -The objective of this work was to estimate the phenotypic diversity in Jafarabadi, Murrah, and Mediterranean buffalo cows (Bubalus bubalis). Thoracic perimeter, withers-and-rump height, body length, and biiliac, external biischiatic, external ilioischiatic, sacropubic, and mean biiliac diameters were measured. The following indexes were calculated: anamorphosis index, pelvic index, withers-to-rump ratio, body index, lateral-body index, relative body index, body capacity indexes 1 and 2, transversal pelvic ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
3
10
0
Order By: Relevance
“…In India, Vohra et al (2015) registered an average FH of 128.66 cm in Gojri buffaloes. In Brazil, Andréa et al (2010) and Rezende et al (2017) both registered an average FH of 139 and 133 cm, respectively, in Murrah buffaloes. In Colombia, Bedoya and Hernández (2013) registered an average FH of 134.50 and an average HH of 137.89 cm in Murrah buffaloes.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In India, Vohra et al (2015) registered an average FH of 128.66 cm in Gojri buffaloes. In Brazil, Andréa et al (2010) and Rezende et al (2017) both registered an average FH of 139 and 133 cm, respectively, in Murrah buffaloes. In Colombia, Bedoya and Hernández (2013) registered an average FH of 134.50 and an average HH of 137.89 cm in Murrah buffaloes.…”
Section: Resultsmentioning
confidence: 94%
“…The THW average was 51.42 cm, being near the average recorded by Vohra et al (2015), which was 53.6 cm per THW for Gojri female buffaloes. Oliveira et al (2001) showed higher values in Murrah crossbred buffaloes (59.0 cm), Ahmad et al (2013) in Nili Ravi buffaloes (56.9 cm), and Rezende et al (2017) in Murrah female buffaloes (58.9 cm). The rump region is responsible for the movement structure of animals and consists of the rump angles.…”
Section: Resultsmentioning
confidence: 95%
“…Morphometric characteristics are the most common criteria for livestock selection (Yilmaz et al 2013) and can be used as qualifying criteria that demonstrate the potential of livestock (Çılek and Petkova 2016). Body analysis has been recorded as a practical approach for investigating the potential of indigenous livestock (de Rezende et al 2017). Data on buffalo body measurements can play an essential role in livestock preservation (Edouard et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Through this analysis, the distribution of animal populations can be described (Lafi et al 2016). A multivariate discriminant is a practical approach for analyzing factors to be measured in livestock (de Rezende et al 2017). In addition to assessing genetic diversity, the analysis of morphometric data can also be used to estimate genetic distances within and between livestock populations to reveal their genetic relationship (Yunusa et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Among the statistical tools applied in animal production, multivariate analysis is an efficient approach used to study compound data for a large number of variables [20]. This technique aims to study several traits simultaneously, which can be difficult to measure or hard for selection programs to understand, especially when there is a negative genetic correlation between them [14].…”
Section: Introductionmentioning
confidence: 99%